The making of measure and the promise of sameness - Lugli, Emanuele 1979- (The University of Chicago Press, 2019)
Measurement is all around us - from the circumference of a pizza to the square footage of an apartment, from the length of a newborn baby to the number of miles between neighboring towns. Whether inches or miles, centimeters or kilometers, measures of distance stand at the very foundation of everything we do, so much so that we take them for granted. Yet, this has not always been the case. This book reaches back to medieval Italy to speak of a time when, far from being obvious, measurements were displayed in the open, showing how such a deceptively simple innovation triggered a chain of cultural transformations whose consequences are visible today on a global scale. Drawing from literary works and frescoes, architectural surveys and legal compilations, Emanuele Lugli offers a history of material practices widely overlooked by historians. He argues that the public display of measurements in Italy's newly formed city republics not only laid the foundation for now centuries-old practices of making, but also helped to legitimize local governments and shore up church power, buttressing fantasies of exactitude and certainty that linger to this day. This ambitious, truly interdisciplinary book explains how measurements, rather than being mere descriptors of the real, themselves work as powerful molds of ideas, affecting our notions of what we consider similar, accurate, and truthful
Keywords: Geschichte; Geschichte 1200-1800; Measurement / Italy / History / To 1500; Measurement / Social aspects / Italy; Metrology / Italy / History / To 1500; Metrology / Social aspects / Italy; Weights and measures / Social aspects / Italy; Metrology / Italy / Historiography; Civilization; Measurement; Metrology; Metrologie; Längeneinheit; Städtebau; Stadtplanung; Vermessung; Maßeinheit; Messbarkeit; Architektur; Italy / Civilization / 1268-1559; Italy; Italien